2007
DOI: 10.1111/j.1468-3083.2007.02146.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction after removal of skin lesions

Abstract: Skin lesion removal, although considered to be a minor procedure, leaves scars that sometimes disturb the patient. According to our study, the most prevalent population for dissatisfaction is females and young males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…Similar to other studies [17,18], we found that the independent assessor was less satisfied with the scar than the participants themselves. Participant satisfaction with torso scars was much higher in our study than in other studies, however [79].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to other studies [17,18], we found that the independent assessor was less satisfied with the scar than the participants themselves. Participant satisfaction with torso scars was much higher in our study than in other studies, however [79].…”
Section: Discussionsupporting
confidence: 90%
“…This is mainly due to the continuous presence of superstitions and low level of knowledge in the field of melanoma [2023, 25, 26]. The results of our study revealed that the surveyed who underwent surgical excision of any skin lesion were often individuals with a large number of so-called solar lentigines, infrequently obeying safe tanning rules and having fragmentary knowledge in that field.…”
Section: Discussionmentioning
confidence: 93%
“…Supposed malignancy, aesthetic causes as well as functional disorders were reported to be the main reasons for surgical excision of skin lesions [25]. Understanding that the total surgical excision is the only efficient way of melanoma treatment was quite common (83.4% of the surveyed) among higher educated respondents and was related to increased skin cancer awareness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemos leído el interesante documento de consenso, publicado en su revista, «Criterios de derivación en hiperplasia benigna de próstata para atención primaria» 1 . Quisiéramos felicitar a los autores por su excelente trabajo y efectuar una consideración respecto al tratamiento con bloqueadores alfa adrenérgicos.…”
unclassified